(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
The results of author’s recent years researches made by the complex of geophysical-geomorphological data and directed to the detection of morphotectonic connections between the Earth’s Crust deeper and surface structures are represented.